2019
DOI: 10.3390/antiox8080302
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Nut Consumption in Middle-Aged and Elderly Population

Abstract: Aging is considered the major risk factor for most chronic disorders. Oxidative stress and chronic inflammation are two major contributors for cellular senescence, downregulation of stress response pathways with a decrease of protective cellular activity and accumulation of cellular damage, leading in time to age-related diseases. This review investigated the most recent clinical trials and cohort studies published in the last ten years, which presented the influence of tree nut and peanut antioxidant diets in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 211 publications
1
31
0
Order By: Relevance
“…Habitual nut intake has long been associated with cardiovascular benefits including reduced risk of cardiovascular disease (CVD) [1], decreased incidence of metabolic syndrome (MetS) [2], and decreased risk of type II diabetes [3]. Tree nuts are an important source of nutrients, containing phytochemicals, antioxidants, and a healthy lipid profile (rich in mono and polyunsaturated fatty acids), all of which are thought to mediate the beneficial cardiovascular and metabolic effects through altered lipid metabolism, antioxidant, and anti-inflammatory mechanisms [4].…”
Section: Introductionmentioning
confidence: 99%
“…Habitual nut intake has long been associated with cardiovascular benefits including reduced risk of cardiovascular disease (CVD) [1], decreased incidence of metabolic syndrome (MetS) [2], and decreased risk of type II diabetes [3]. Tree nuts are an important source of nutrients, containing phytochemicals, antioxidants, and a healthy lipid profile (rich in mono and polyunsaturated fatty acids), all of which are thought to mediate the beneficial cardiovascular and metabolic effects through altered lipid metabolism, antioxidant, and anti-inflammatory mechanisms [4].…”
Section: Introductionmentioning
confidence: 99%
“…PSO has a lot of beneficial health effects as an antibacterial against gram-negative and gram-positive germs (Borate et al, 2014), antioxidant (Xiao et al, 2010), anti-inflammatory modulating the inhibition of proinflammatory cytokines (Lee et al, 2012), antimycobacterial (Khushboo et al, 2010), antipsoriatic (Dwarampudi et al, 2012), and antidepressant (Yi et al, 2008). Besides, PSO possesses osteoblast proliferation-stimulating effects (Larsson and Fazzalari, 2014), estrogenic-like effects (Xin et al, 2019), and antitumor properties (Szliszka et al, 2011;Luo et al, 2013;Pal et al, 2017a;Badarau et al, 2019;Rusu et al, 2019). PSO is a natural phenolic coumarin in the same class with isopsoralen, psoralen, bakuchiol, bakuchalcone, flavones, and bavachinin (Zhang et al, 2016) isolated and identified from the seeds of the medicinal plant Cullen corylifolium.…”
Section: Introductionmentioning
confidence: 99%
“…Nuts have numerous biologically active compounds, including carotenoids, polyphenols, phytosterols, vitamins, minerals, and fiber. The antioxidant and anti-inflammatory properties of these substances might act synergistically in lowering risk factors related to some age-related diseases and highlight the importance of including nuts in a healthy diet [5].The most common edible nuts are walnuts, almonds, hazelnuts, and peanuts. These four types represent 95% of the total nut intake in the Spanish population [6].…”
mentioning
confidence: 99%